2011
DOI: 10.1002/bab.10
|View full text |Cite
|
Sign up to set email alerts
|

In situ endothelialization of intravascular stents from progenitor stem cells coated with nanocomposite and functionalized biomolecules

Abstract: Abstract.Owing to their noninvasive nature, coronary artery stents have become popular demand for patients undergoing percutaneous coronary intervention. Late restenosis, in-stent restenosis, and late thrombosis, all mediated by the denuded endothelium, represent the most recurrent failures of vascular stent induction. Higher patency rates of stents can be achieved by restoring the native internal environment of the vessel-an endothelium monolayer. This active organ inhibits the inflammatory reaction to injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 106 publications
(134 reference statements)
0
24
0
Order By: Relevance
“…To meet the essential requirements for these applications, we have developed nanocomposite materials by copolymerization of POSS monomers with poly(carbonate urea)urethane (POSS-PCU) to form covalently modified and cross-linked nanostructures within the hard segments, and form pendant chain groups. [10,[50][51][52][53] Studies on its cytocompatibility, anti-thrombogenicity, and biostability have shown that this nanocomposite polymer has unique characteristics for applications at the blood-biomaterial interface. [52] This nanocomposite polymer can be biofunctionalized by anchoring peptides and growth factors through surface modification in order to attract endothelial progenitor cells (EPCs) from the circulatory blood, and become endothelialized to enhance the bio-and haemocompatibility of cardiovascular devices made with this material ( Figure 2).…”
Section: Poss Nanocomposites In Cardiovascular Implantsmentioning
confidence: 99%
“…To meet the essential requirements for these applications, we have developed nanocomposite materials by copolymerization of POSS monomers with poly(carbonate urea)urethane (POSS-PCU) to form covalently modified and cross-linked nanostructures within the hard segments, and form pendant chain groups. [10,[50][51][52][53] Studies on its cytocompatibility, anti-thrombogenicity, and biostability have shown that this nanocomposite polymer has unique characteristics for applications at the blood-biomaterial interface. [52] This nanocomposite polymer can be biofunctionalized by anchoring peptides and growth factors through surface modification in order to attract endothelial progenitor cells (EPCs) from the circulatory blood, and become endothelialized to enhance the bio-and haemocompatibility of cardiovascular devices made with this material ( Figure 2).…”
Section: Poss Nanocomposites In Cardiovascular Implantsmentioning
confidence: 99%
“…Theoretically, rapid endothelialization of the luminal surfaces of stents is a way of increasaing implant patency and preventing in-stent stenosis by inhibiting both thrombosis and intimal hyperplasia [39]. Recent studies focus on the immobilization of endothelial progenitor cell (EPC) specific antibodies for circulating EPC capturing [40]. Many in vitro and in vivo studies have already successfully induced EPC incorporation onto target sites, and the immobilized EPCs have been observed to be differentiated and proliferated into an EC monolayer [41].…”
Section: In Situ Endothelializationmentioning
confidence: 99%
“…It does not cause inflammatory reactions in the surrounding host tissue [46][47][48][49]. Experiments in cardiac implants also prove that POSS-PCU has a fine quality of calcification resistance (Alobaid et al, 2006;Motwani et al, 2011). POSS-PCU has already been used first-in-human studies as a bypass graft [50], lacrimal duct [51] and the world's first synthetic trachea [52,53].…”
Section: Polyhedral Oligomeric Silsesquioxane Polycaprolactone-urea Umentioning
confidence: 99%
“…Studies on polyhedral oligo silsesquioxanes (POSS) were limited to conjugation with fluorescent dyes [5], incorporation into dendrimeric systems [6,7], development of dental nano-composites [8] and cardiovascular implants [9]. Silsesquioxanes were scarcely studied as drug delivery systems and never as moieties covalently conjugated with drugs, even though they are free of the disadvantages of polymers as polydispersity of hyperbranched polymers or laborious syntheses of dendrimers.…”
Section: Introductionmentioning
confidence: 99%